Agricultural Tariffs or Subsidies : Which Are More Important for Developing Economies? - Hoekman, Bernard; Ng, Francis; Olarreaga, Olarreaga (Washington, DC: World Bank, 2014)
This article assesses the impact of the world price-depressing effect of agricultural subsidies and border protection in Organization for Economic Co-operation and Development (OECD) countries on developing economies' exports, imports, and welfare. Developing economy exporters are likely to benefit from reductions in such subsidies and trade barriers, whereas net importers may lose as world prices rise. A simple partial equilibrium model of global trade in commodities that benefit from domestic support or export subsidies is developed to estimate the relevant elasticities. Simulation results suggest that a 50 percent reduction in border protection will have a much larger positive impact on developing economies' exports and welfare than a 50 percent reduction in agricultural subsidies. Although there is significant heterogeneity across developing economies, the results suggest that efforts in the Doha round of World Trade Organization (WTO) negotiations should be directed at substantially reducing border protection.